Hydrochemical composition, conditions and formation factors in the Pontian aquifer groundwater within the Odesa city territory - Oprits, Hanna; Poltavchenko, Yelyzaveta; Shatalin, Serhii; Horban, Dmytro (Journal of Education, Health and Sport, 2025)
This study examines the hydrochemical characteristics of groundwater formation in the Pontian aquifer located beneath the city of Odesa, Ukraine, in the context of prolonged and intensive anthropogenic influence. Drawing on over 300 hydrochemical analyses conducted between 1971 and 2014, the research identifies significant changes in the chemical composition of groundwater over time. Key findings indicate a wide range of mineralization levels (0.7–10 g/dm³) and a consistent dominance of sulfate and sodium-magnesium ions. A noticeable upward trend in mineralization has been recorded in the majority of wells, suggesting increased anthropogenic stress caused by domestic wastewater infiltration, leakage from water supply systems, and inter-aquifer flow. Furthermore, the study highlights a strong correlation between elevated sulfate concentrations and the intensification of karst formation processes in limestone formations. These findings carry important implications for the management of underground infrastructure and the development of effective water resource protection strategies for the Odesa city.